(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2014)
Studies in Land and Credit in Ancient Athens 500-200 B.C.: The Horos Inscriptions was published by Rutgers University Press in 1952 and was reprinted with a new introduction by Paul Millett by Transaction Books in 1985. The book is unlike Finley’s other books, which were based on lectures. The World of Odysseus had its origins in a series of lectures given at Bryn Mawr College. Democracy Ancient and Modern was based on the Mason Welch Gross Lectures given in New Brunswick, New Jersey in April 1972. 5 The Ancient Economy was the publication of Finley’s Sather Lectures given at the University of California, Berkeley in the Winter Quarter of 1972. Ancient Slavery and Modern Ideology was based on four lectures presented at the Collège de France in November and December 1978. Politics in the Ancient World was the publication of his Wiles Lectures delivered at the Queen’s University, Belfast in May 1980.8 All of these works were written for the general public and address broad, general topics in Ancient History: there is little detailed analysis of the ancient sources, and the bibliographies in some cases contain few items.